Performance of Bond Ladder Strategies: Evidence from a Period of Low Interest Rates - Christoph Schmidhammer (Credit and Capital Markets – Kredit und Kapital, 2018)
Based on German government bond yields, this paper analyses the performance of laddered strategies during a period of low interest rates. Relying on the REX, Germany"s leading bond index, laddered cash flows are created, and maturity structures are systematically changed. A constructed rolling window of annual returns reveals that risk and return significantly increase with the length of maturity. Performance measures, such as return on risk-adjusted capital and the Sharpe ratio, show that long-term bond ladders significantly dominate short-term ladders. However, for upward movements in the average yield level, the dominance is reduced. The results imply that portfolio managers should consider performance characteristics in maturity decisions as well as expectations of changes in the yield level. – – Performance gestaffelter Anlagestrategien in einer Niedrigzinsphase Die aktuelle Studie analysiert die Performance gestaffelter Anlagestrategien in einem Niedrigzinsumfeld. Die Auswertungen basieren auf der Renditestruktur von Bundeswertpapieren. In Anlehnung an die Laufzeitstruktur des Deutschen Rentenindex REX werden Bondportfolios als gleitende Durchschnitte unterschiedlicher Laufzeiten erzeugt und deren Fristigkeit systematisch verändert. Auf Basis einer rollierenden Ermittlung von Renditen wird gezeigt, dass Risiko und Ertrag mit zunehmender Maximallaufzeit steigen. Dies trifft auch signifikant auf die Performancemaße Return on Risk Adjusted Capital und Sharpe Ratio zu. Für steigende Renditeniveaus ist die Dominanz langfristiger Laufzeitstrukturen jedoch schwächer ausgeprägt. Portfoliomanager sollten daher bei der Auswahl der Laufzeiten neben der Performance auch die Erwartungen an Renditestrukturänderungen berücksichtigen.
Keywords: E43; G11; G12; G21; 330; Maturity; Fixed-Income Portfolios; Period of Low Interest Rates; Bond Ladders; Return; Risk; Performance; RORAC; Sharpe Ratio